2021
DOI: 10.3389/fphar.2021.699191
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Dosing Regimens of Meropenem in Septic Children Receiving Extracorporeal Life Support

Abstract: Objectives: To develop a population pharmacokinetic model of meropenem in children with sepsis receiving extracorporeal life support (ECLS) and optimize the dosage regimen based on investigating the probability of target attainment (PTA).Methods: The children with sepsis were prospectively enrolled in a pediatric intensive care unit from January 2018 to December 2019. The concentration-time data were fitted using nonlinear mixed effect model approach by NONMEM program. The stochastic simulation considering var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 35 publications
3
10
0
Order By: Relevance
“…The most frequently studied drug in children receiving CRRT was meropenem, accounting for nine of the included studies ( 4 , 5 , 26 32 ). Vancomycin followed with three included studies ( 33 35 ).…”
Section: Resultsmentioning
confidence: 99%
“…The most frequently studied drug in children receiving CRRT was meropenem, accounting for nine of the included studies ( 4 , 5 , 26 32 ). Vancomycin followed with three included studies ( 33 35 ).…”
Section: Resultsmentioning
confidence: 99%
“…This is mostly due to meropenem’s chemical characteristics. According to Wang et al ’s study 23 about a popPK model of meropenem in children with sepsis receiving extracorporeal life support, the PK characteristics of meropenem were not affected by ECMO intervention. Furthermore, ECMO and CRRT can raise Vd due to the extracorporeal circuits, although this study indicated that the impact on meropenem concentration was smaller than previously documented haemofilters.…”
Section: Resultsmentioning
confidence: 99%
“… 40 The differences in Vd and Cl of some of the studied drugs, such as vancomycin, between ECMO and non-ECMO controls demonstrated significant intrastudy variability, with some studies showing increased values for the PK parameters, 31 32 36 while others showed decreased values or no change. 23 24 41 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations